Accuracy of Clinical Examination versus MRI in the Diagnosis of Anterior Cruciate Ligament Tears taking Arthroscopic Examination as Gold Standard (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the accuracy of clinical examination versus MRI in the diagnosis of ACL tears taking arthroscopic examination as gold standard. Design: Cross sectional survey. Place and Duration of Study: This study was conducted in the department of Orthopedics, Sir Ganga Ram Hospital, Lahore from June 2013 to September 2014. Patients and Methods: In this study, a total of 108 patients suspected of ACL injury presenting in the outdoor of Orthopedic Department, Sir Ganga Ram Hospital, Lahore who subsequently underwent arthroscopy were included. A detailed clinical examination was done to assess ACL status prior to MRI. Findings of clinical examination and MRI were noted. Arthroscopic findings were taken as gold standard and clinical examination and MRI were judged accordingly. A written informed consent was taken from every patient. Results: The mean age of the patients was 28.81±5.33 years while majority (n=103, 95.4%) patients were male and only 5 (4.6%) were female. Arthroscopy was positive in 62 (57.41%) patients while in the remainder 46 (42.59%) patients it revealed intact ACL. The sensitivity, specificity, accuracy, positive predictive value and negative predictive values of clinical examination were 98.39%, 91.30%, 95.37%, 93.85% and 97.67% respectively and those for MRI were 98.39%, 82.61%, 91.67%, 88.41% and 97.44% respectively. Conclusion: According to the results of our study, both the clinical examination and MRI are extremely sensitive and accurate in the diagnosis of ACL tear. However, due to higher false positive rate and cost, MRI should be reserved only for doubtful cases or where concomitant other injuries are suspected.
Keywords: ACL Tear, Diagnostic Accuracy of Clinical Examination, Diagnostic Accuracy of MRI